Additive solution‐7 reduces the red blood cell cold storage lesion. Issue 3 (19th September 2014) - Cancelas, Jose A.; Dumont, Larry J.; Maes, Lou A.; Rugg, Neeta; Herschel, Louise; Whitley, Pamela H.; Szczepiokowski, Zbigniew M.; Siegel, Alan H.; Hess, John R.; Zia, Majid
<x xml:space="preserve">Abstract</x> Background Transfusion of long‐stored red blood cells (RBCs) is associated with decreased in vivo RBC recovery, delivery of RBC breakdown products, and increased morbidity and mortality. Reducing the burden of this RBC "storage lesion" is a major challenge in transfusion medicine. Additive solution‐7 (AS‐7) is a new RBC storage solution designed to improve RBC metabolism by providing phosphate and increasing buffering capacity. Study Design and Methods Storage quality in AS‐7 was measured in a prospective, randomized, three‐center trial using units of whole blood from healthy human subjects whose RBCs were stored for up to 56 days in AS‐7 (n = 120) or for 42 days in the control solution AS‐1 (n = 60). Results Hemolysis and shedding of protein‐containing microvesicles were significantly reduced in RBCs stored in AS‐7 for 42 and 56 days compared with RBCs stored in AS‐1. Autologous in vivo recoveries of RBCs stored in AS‐7 was 88 ± 5% at 42 days (n = 27) and 82 ± 3% at 56 days (n = 27), exceeding recoveries of RBCs stored in currently used solutions. Conclusion Increasing the phosphate, pH range, and buffer capacity of a RBC storage system allowed RBCs to be stored better and longer than currently approved storage systems. AS‐7 ameliorates the long‐term storage lesion resulting in significantly increased viability in vitro and in vivo.